Electrochemical degradation of dye on lead dioxide electrodeposited on stainless steel: effect of cyclic voltammetry parameters. Issue 46 (1st October 2016) - Elaissaoui, Ines; Akrout, Hanene; Bousselmi, Latifa
Abstract: The effect of cyclic voltammetry (CV) on electrochemical behavior of PbO2 layer electrodeposited by pulsed method on stainless steel (AS30) has been studied. The field emission scanning electrons microscope and X-ray diffraction (XRD) were used to characterize the surface morphology and crystal structure of different electrodes with CV effect, respectively. The content of PbO2 particles has been tuned by altering the cycle number, of CV through which the content of PbSO4 also increased. It is related to reduction phenomena depending on electron transfer through the pores into β-PbO2 layer. Electrochemical behavior of the prepared samples was investigated in 0.5 M H2 SO4 solution by CV and electrochemical impedance spectroscopy (EIS) techniques. EIS results revealed that the charge-transfer resistance significantly increased because the lead sulfate layer is more compact and the access of electrolyte ions to the internal layer is blocked. Anodic oxidation of solutions containing Amaranth as a dye model was studied to evaluate the use of these electrodes as anodes in environmental issue. After five cycle of CV, PbO2 film becomes more resistive according to value of R f and this may have a deleterious effect on the electrochemical degradation activity compared to that without CV treatment. Based on the obtained results, after electrolysis time of 5 h at acidic pH medium, the color and the chemical oxygen demand removals on PbO2 electrode treated by 1 CV achieved nearly to 97 and 83%, higher than that without CV treatment (77 and 47%), respectively.